Urinary tract infections are common and have an impact on performance in elite wheelchair athletes: a cross-sectional study of self-reported data (Swiss Medical Weekly, 2025)
STUDY AIMS: Wheelchair athletes may be at risk of urinary tract infections, especially those with spinal cord injury. A urinary tract infection can lead to a loss of training hours and reduced performance in athletes. We assessed the self-reported occurrence of urinary tract infections and the impact of urinary tract infections on training and performance in elite wheelchair athletes. We also evaluated the prophylactic measures used, as reported by the athletes.METHODS: Data were collected from September 2022 to August 2023 at an institute specialised in examining wheelchair athletes. All wheelchair athletes active in international and/or national competitions who attended one of the routine checkups at the institute during the study period were included. The number of self-reported urinary tract infections during the previous 12 months was collected, including symptoms associated with urinary tract infections, prophylaxis, and impact on training and performance. The method of bladder voiding was assessed by catheter use, either “Yes” (intermittent and indwelling) or “No” (no catheter use at all).RESULTS: Eighty-one athletes were included (mean ± standard deviation age 35±11 years; 24 females; 67 with spinal cord injury; 56 using a catheter). Prophylaxis was used by 38 (47%) athletes; the most common was natural supplements, including cranberry juice and D-mannose. Thirty-six (44%) athletes had had at least one urinary tract infection during the previous 12 months. Athletes were more likely to have had at least one urinary tract infection if they had spinal cord injury (34 [94%] vs 2 [6%] athletes, p = 0.013) or were using a catheter (32 [89%] vs 4 [11%] athletes, p = 0.001). A urinary tract infection resulted in 4±6 lost training days and impaired performance.CONCLUSION: Urinary tract infections are common in elite wheelchair athletes and have a negative impact on training volume and performance. About half of the athletes use prophylaxis. Athletes with spinal cord injury or who use a catheter are especially at risk of urinary tract infections.